Resposta de lisianthus (Eustoma grandiflorum (Raf.) Shinn.) ao manejo de irrigação, uso de polímero hidroretentor e época de cultivo em ambiente climatizado - Piroli, Jéssica Dariane (2022)
No flower segment, or lisianthus, is configured as one of the most important species in the national and international market. However, knowledge of the correct irrigation and the factors that harmed production and effort has generally been based on empiricism, on the application of water in insufficient quantity or of insufficient quality. Thus, an alternative capable of optimizing the efficiency in the use of water is the addition of a hydroretainer (hydrogel) to the substrate, associated with irrigation, in order to absorb a large amount of water, being used as an alternative to improve water storage under conditions of water deficit. In addition, it is essential to study post-harvest reference technologies, since cut flowers are highly perishable products. Thus, the objective of the present work was to identify and quantify the influence of water management and hydrogel use, also considering an influence of the growing season on production, consumption, water use efficiency, root growth, quality and durability. in the lisianthus culture. The experimental design adopted was completely randomized, in a twofactor 5x4 scheme, with four replications. The treatments consisted of water capacity levels (40, 60, 80, 100 and 120% of water capacity) and four hydrogel doses (0, 3, 6 and 9 grams per pot). In short, the amplitude is greater than the hydroretainer of the hydrogel did not work as the water stress on the plants, however, the responses, which configured the best in terms of height, diameter and production of control of floral pressures of lisianthus were as irrigation ones. Irrigation depths of approximately 80% of the potting capacity are more suitable for the growth and production of lisianthus. The water consumption showed an increasing behavior, both with the increase of the hydrogel dose, and with the increase of the irrigation level, in the two growing seasons. The efficiency of water use, in the first season, had a constant growth until the water depth of 80% of the vessel's retention capacity, and hydrogel doses between 3 and 6 grams. In the second season, the best results were found between 60% and 100% slides, regardless of the hydrogel dose tested. The total length, surface area and root volume of lisianthus plants showed better results when blades between 60 and 100% of CRV were used. The use of sucrose + citric acid is efficient in maintaining the quality and post-harvest durability of lisianthus floral stems.